Sebuah FUNETHNOMATH: Pengembangan Media Pembelajaran Web Virtual Reality Tour Dengan Pendekatan Etnomatematika: FUNETHNOMATH: Development of Virtual Reality Tour Web Learning Media With an Ethnomathematic Approach - Nur Hasanah; Purnomo, Eko Andy; Venissa Dian Mawarsari (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
This research aims to develop a funethnomath learning media based on a virtual reality tour in the form of a website using a valid ethnomathematics approach. This research is a development type or RnD with the ADDIE model, consisting of the stages of analysis, design, development, implementation, and evaluation, which is limited to the development stage. Data collection techniques include interviews, observations, documentation, and questionnaires. The validation questionnaire is given to material and media experts. The research instrument uses a validation questionnaire for media and material experts. The media expert validation questionnaire has several assessment aspects, including appearance, software engineering, and visual communication. The material expert validation questionnaire has several assessment aspects, including material design and language. The data analysis of the questionnaire is determined according to the media validity assessment guidelines. The results of this study show that the developed media has valid criteria with a final score of 3.015 in the media expert validation with assessment aspects of appearance, software engineering, and visual communication, and a final score of 3.0625 in the material expert validation with assessment aspects of material design and final value.